Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.2139/ssrn.2691027
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic Income and Conditional Generosity

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Credit growth plays an important role in stimulating economic growth and is strongly associated with faster economic growth [68,69]. An interesting experiment by Kellner et al [70] showed that when people knew their income would increase, their donations would be higher. This means that credit growth indirectly increases the generosity of society by stimulating economic growth.…”
Section: Moderating Hypothesismentioning
confidence: 99%
“…Credit growth plays an important role in stimulating economic growth and is strongly associated with faster economic growth [68,69]. An interesting experiment by Kellner et al [70] showed that when people knew their income would increase, their donations would be higher. This means that credit growth indirectly increases the generosity of society by stimulating economic growth.…”
Section: Moderating Hypothesismentioning
confidence: 99%
“…It may also be possible to combine such strategies. Just as Thaler and Benartzi (2004) found that participants increased retirement savings contributions dramatically when allowed to (1) pledge in advance to contribute (2) a share of potential future raises, so Kellner et al (2015) found that participants increased charitable contributions when allowed to (1) pledge in advance to contribute (2) a share of a potential future winnings.…”
Section: "Manage Decision Avoidance" [Relative To Its Alternatives]mentioning
confidence: 99%
“…It has been run in more than one hundred published papers over the last three decades (Engel, 2011), consistently demonstrating violations of the selfishness axiom. Moreover, given that dictator games are susceptible to numerous types of framing effects (Brañas-Garza, 2007;Zizzo, 2010), we contend that any test of invariance to framing effects should include a dictator game, especially in the light of several recent contributions that suggest that people's choices in dictator games change when the probability of realizing the decision changes (e.g., Kellner et al, 2015;Brock et al, 2013). In this work, we analyse how certainty in regard to the realization of expected pay-offs impacts pro-social behaviour.…”
Section: Introductionmentioning
confidence: 99%